Patient-Reported Outcome of Surgical Treatment of Nerve Entrapments in the Proximal Forearm. (11th September 2011) - Svernlöv, Birgitta; Nylander, Göran; Adolfsson, Lars
Abstract : The outcome of decompression for long-standing symptoms of nerve entrapments in the proximal forearm was investigated in a retrospective study of 205 patients using a self-assessment questionnaire, 45 months after the operation. The questionnaire consisted of visual analogue scale recordings of pre- and postoperative pain during rest and activity, questions about remaining symptoms and appreciation of the result and the Disabilities of Arm, Shoulder and Hand form (DASH). Altogether, 59% of the patients were satisfied, 58% considered themselves improved, and 3% as being entirely relieved of all symptoms. Pain decreased significantly (P = 0.001 ). There was a significant correlation between preoperative duration and patient perceived post-operative pain. Preoperative pain was a chief complaint, and pain reduction appears to be the principal gain of the operation. Although the majority of the patients benefited from the operation, a substantial proportion was not satisfied. There is apparently room for improvement of the diagnostic and surgical methods applied in this study.